Suspected Adnexal Torsion in Qatar – Symptomatology Reliability in Diagnosis and Management - Morounfolu Thompson (17045472) (2024)
Background In Qatar, primary presentation of acute abdominal pain with most women is to the Emergency Department. Adnexal torsion is a rare time limiting surgical emergency with severe reproductive health consequences characterised by such a presentation, and firm diagnosis requires direct visualization at surgery.1 Accurate, timely diagnosis of adnexal torsion is crucial to predict the need for surgery and prevent complications, however information on signs and symptomatology reliability is limited in the medical literature. There is currently no relevant reported data from Qatar. Methods This study aimed to assess symptomatology reliability in prediction of surgically proven cases of suspected adnexa torsion presenting to Al Wakra Hospital in Qatar. A database review was conducted of all women with suspected adnexal torsion presenting to the Emergency Departments between 1st January 2017 and 31st December 2022. Clinical data were assessed following a literature review. Sensitivity, specificity and predictive estimates were calculated for each parameter with 95% confidence intervals (CI) included. Results Among 58 suspected cases, 39 (67.24%) were subsequently confirmed as adnexal torsion. The predominating symptomatology was: acute abdominal pain associated with vomiting, abdominal guarding, mass, and tenderness (Figure 1). Tachypnoea was absent in all suspected cases (Table 1). Abdominal tenderness had a very high sensitivity, 99.2% (CI 97.6-99.8%) and positive predictive value, 96.0% (CI 95.1-96.8), while the absence of vaginal bleeding showed a high specificity, 100% (CI 82.4-100%). Conclusion Emergency room presentation and triage of cases with suspected adnexal torsion for surgery can be improved using these study findings. The wide confidence intervals in some parameters reflects the wide variation in clinical presentation and current diagnostic uncertainty.3 It is interesting that tachypnoea does not appear to be a feature in our population while abdominal tenderness is a strong predictor especially when linked with absence of vaginal bleeding.